New light on ancient enzymes – in vitro CO2 Fixation by Pyruvate Synthase of Desulfovibrio africanus and Sulfolobus acidocaldarius. (19th July 2019) - Witt, Andreas; Pozzi, Roberta; Diesch, Stephan; Hädicke, Oliver; Grammel, Hartmut
Abstract : Two variants of the enzyme family pyruvate:ferredoxin oxidoreductase (PFOR), derived from the anaerobic sulfate‐reducing bacterium Desulfovibrio africanus and the extremophilic crenarchaeon Sulfolobus acidocaldarius, respectively, were evaluated for their capacity to fixate CO2 in vitro . PFOR reversibly catalyzes the conversion of acetyl‐CoA and CO2 to pyruvate using ferredoxin as redox partner. The oxidative decarboxylation of pyruvate is thermodynamically strongly favored, and most previous studies only considered the oxidative direction of the enzyme. To assay the pyruvate synthase function of PFOR during reductive carboxylation of acetyl‐CoA is more challenging and requires to maintain the reaction far from equilibrium. For this purpose, a biochemical assay was established where low‐potential electrons were introduced by photochemical reduction of EDTA/deazaflavin and the generated pyruvate was trapped by chemical derivatization with semicarbazide. The product of CO2 fixation could be detected as pyruvate semicarbazone by HPLC‐MS. In a combinatorial approach, both PFORs were tested with ferredoxins from different sources. The pyruvate semicarbazone product could be detected with low‐potential ferredoxins of the green sulfur bacterium Chlorobium tepidum and of S. acidocaldarius whereas CO2 fixation was not supported by the native ferredoxin of D. africanus . Methylviologen as an artificial electron carrier also allowed CO2 fixation. For both enzymes, the results are the first demonstration of CO2 fixation in vitro . Both enzymes exhibited high stability in the presence of oxygen during purification and storage. In conclusion, the employed PFOR enzymes in combination with non‐native ferredoxin cofactors might be promising candidates for further incorporation in biocatalytic CO2 conversion. Enzymes: EC1.2.7.1 . Pyruvate:Ferredoxin Oxidoreductase Abstract : Pyruvate:ferredoxin oxidoreductase may provide attractive opportunities for conversion of CO2 in biocatalytic processes. Here we demonstrate that two enzymes obtained from anaerobic sulfur bacteria and acidothermophilic archaea, respectively, can be operated as CO2 ‐fixing pyruvate synthase in vitro when combined with low‐potential ferredoxins or methylviologen. A photobiochemical assay is described where light‐activated deazaflavin serves as electron source and chemical derivatization of pyruvate drives the reaction in the CO2 ‐fixing direction.